Differential expression of protein kinase C isoforms in diethylnitrosamine-initiated rat liver - Lee, YS; Hong, SI; Lee, MJ; Kim, MR; Jang, JJ (ELSEVIER SCI IRELAND LTD, 1998)
Although protein kinase C (PKC), a family of 12 related isoforms, plays an important role in carcinogenesis, little is known about the specific role of each isoform in the initiation stage of hepatocarcinogenesis. The subcellular distribution of PKC isoforms in the early stages of diethylnitrosamine (DEN)-initiated hepatocarcinogenesis was therefore examined. Three-week-old female Sprague-Dawley rats were intraperitoneally injected twice in 1 week with DEN; all animals were sacrificed at 1, 2 and 24 h and 3 and 7 days after the second injection, PKC alpha and -beta expression in both cytosolic and particulate fractions decreased as a result of 1 h of DEN treatment and this effect lasted for 7 days. In both fractions, PKC epsilon expression showed a marked increase by DEN treatment, while the expression of PKC delta and -zeta was almost unchanged. These results suggest that differential expression of PKC isoforms may play an important role in the early stage of DEN-initiated hepatocarcinogenesis in rats. Published by Elsevier Science Ireland Ltd.
Keywords: HA-RAS; ISOZYMES; FAMILY; CELLS; HEPATOCARCINOGENESIS; TRANSFORMATION; TUMORIGENICITY; ACTIVATION; PAPILLOMAS; MEMBRANE